Assessing the Impact of Terra Preta from Rice Husk on Soil, Rice Plant Growth, and Yield in the System of Rice Intensification (SRI) - Adrinal, Adrinal (JOURNAL OF TROPICAL SOILS, 2025)
The practice of intensive rice field cultivation and the excessive application of chemical fertilizer often lead to issues such as a gradual decline in soil quality and fertility, as well as enviromental pollution. By employing Tetadi as ameliorant technology and adopting SRI cultivation techniques, it is hoped that we can mitigate the negative effects on rice fields. This study was aimed to examine the effect of Tetadi on physical properties of paddy soil, growth, and rice yield on SRI method. The experiments were conducted in paddy fields in Pasar Ambacang, Kuranji, Padang city, and the experimental were application of Tetadi A=0 tons/ha, B=5 tons/ha, C= 10 tons/ha, D= 15 tons/ha, E= 20 tons/ha. The data were compared to the criteria of soil physical properties and plant data were statistically analysed for the variance. The results showed that the change has an insignificant impact on soil physical properties, yet decrease BD by 28.2%; increase SOM by 18.55%; TRP by 13.7%, moisture content 5.6%; permeability by 34.2%, and PAT by 20%. Application of 20 tons/ha Tetadi increased number of productive saplings 52.65% as well as the yield by 69.46% compared to the treatment without Tetadi application.